NEPHROLOGIST'S PRACTICAL ADVICE - T.V. Sergeeva; N.N. Kartamysheva; A.G. Timofeeva (Union of pediatricians of Russia, 2008)
Pathology of kidneys and urinary tracts are some of the most widespread in infancy. The «discreet» course of a number of diseases quite often results in diagnostics only at the stage of progression into chronic kidney insufficiency. It is very important to notice the changes in the condition of a child and consult the nephrologist. In this article authors cover relevant issues of diagnostics and treatment of children with pathology of kidney and urinary tract.Key words: kidney diseases, diagnostics, children.